The effectiveness of regulatory capital requirements prior to the onset of the financial crisis - Abreu, J. F.; Gulamhussen, M. A. (International Review of Finance, 2015)
We extend the literature on the role of capital requirements as a regulatory tool by developing a continuous measure of the degree of regulatory pressure and by examining data on US commercial banks during the economic upturn that preceded the 2007–2009 ?nancial crisis. Our ?ndings indicate the inability of regulatory pressure to force banks to build capital buffers during the economic upturn that preceded the crisis. These ?ndings are consistent with the view that banks entered the crisis with inadequate levels of capital. Our ?ndings support the endeavors of regulators in explicitly demanding capital buffers in their new regulatory framework.